2019
DOI: 10.3390/ijerph16091546
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the HLA-G Polymorphism and sHLA-G Levels in Parental Pairs with High-Risk Pregnancy

Abstract: Human leukocyte antigen G (HLA-G) is observed in immune system cells and other organs. It is a class Ib molecule, which plays a pivotal role in the implantation and maintenance of pregnancy. The aim of this study was to assess the relationship between serum sHLA-G levels and the HLA-G allele in parental pairs with complicated obstetric histories. The clinical material consisted of 210 women and 190 men with the experience of a complicated or an unsuccessful pregnancy. The control group included parents―89 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…sHLA-G, a soluble molecule, can be detected in pregnant women in all three trimesters. During the first trimester, this molecule plays an important role during the implantation process as it can regulate the activity of immune cells, such as NKs and cytotoxic T lymphocytes in the decidua, ensuring antigen tolerance [ 31 ]. The maternal sHLA-G concentration in patients who delivered at term by c-section showed that its levels continue to increase as labor progresses.…”
Section: Introductionmentioning
confidence: 99%
“…sHLA-G, a soluble molecule, can be detected in pregnant women in all three trimesters. During the first trimester, this molecule plays an important role during the implantation process as it can regulate the activity of immune cells, such as NKs and cytotoxic T lymphocytes in the decidua, ensuring antigen tolerance [ 31 ]. The maternal sHLA-G concentration in patients who delivered at term by c-section showed that its levels continue to increase as labor progresses.…”
Section: Introductionmentioning
confidence: 99%
“…28 articles were assessed for eligibility ( 8 , 19 , 35 , 38 , 39 , 41 , 42 , 50 – 70 ). 21 articles were excluded from systematic review and meta-analysis [nine are reviews ( 38 , 51 58 ), nine cases are not RIF patients ( 59 – 67 ), and three studies did not measure the sHLA-G levels ( 39 , 42 , 50 )]. Four studies are excluded from quantitative analysis for reasons [three articles’ data are not available to extract for synthesis ( 8 , 68 , 69 ), one study measured sHLA-G levels in the endometrium by semi-quantitative method ( 41 )].…”
Section: Resultsmentioning
confidence: 99%
“…18 articles were assessed for eligibility. Eight articles were excluded from the systematic review [five were reviews ( 57 , 58 , 71 73 ), two were conference abstracts without data ( 74 ), and cases in one study were not IVF patients ( 59 )]. Six studies were excluded from the quantitative meta-analysis [three studies’ data are not available to extract for synthesis ( 19 , 41 , 75 ), three articles reported the polymorphism in only one study thus cannot be synthesized ( 8 , 70 , 76 )].…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] Indeed, studies have suggested a correlation between lower sHLA-G levels in cord blood and recurrent spontaneous abortion, gestational diabetes mellitus, and preeclampsia. [ 5 6 ] Moreover, HLA-G is expressed by the thymus medulla, pancreatic islets, and cornea in the steady state; during stress, cancer, or inflammation, HLA-G expression is triggered in several tissues. [ 1 7 ]…”
Section: Introductionmentioning
confidence: 99%